Consorciação de cultivares de caupi-hortaliça com cultivares de cenoura em sistema orgânico - Costa, Arnaldo Pantoja da (2014)
This study aimed to evaluate the agroeconomic performance of the intercropping system of cowpea-vegetable cultivars with carrot cultivars fertilized with roostertree in the semi-arid conditions of Mossoró-RN. The work was conducted at the Experimental Farm "Rafael Fernandes" of the Universidade Federal Rural do Semi-Àrido (UFERSA) during the period of September 2013 to March 2014. The experimental design was a randomized complete block with four replications and treatments arranged in a factorial 4 x 2, resulting from the combination of four cowpea-vegetable cultivars of (BRS Tumucumaque, BRS Cauamé, BRS and BRS Guariba Itaim) with two carrot cultivars (Brasilia and Alvorada). In each block was planted a plot of each cultivar in sole crop. All treatments were fertilized with roostertree at a dose of 50.37 t ha-1. The characteristics evaluated in the cowpea-vegetable crop were: number of green pods per area, yield of green pods and dry weight of green pods, number of green grains per pod, productivity green of grains, weight of 100 green grains and dry weight of green grains. In the carrot were evaluated: plant height, fresh and dry mass of shoots, total and commercial productivity and classified productivity of roots. The competition and agroeconomic efficiency indices of intercropping systems evaluated were: Aggressivity, competitive ratio, intercropping advantage, land equivalent ratio, productive efficiency index, score of the canonical variable, gross income, net income, rate of return, profit margin and modified monetary advantage. The cultivar of carrot that had the best performance in the commercial production of roots was the "Brasilia", both in sole crop as in intercropped with cowpea-vegetable cultivars. In absolute terms, the cultivar of cowpea-vegetable of higher productivity was BRS Tumucumaque both single crop and intercropping system. The cultivars combination of higher agronomic/biological efficiency was the BRS Guariba with carrot Alvorada and of the greater economic efficiency was the cultivar BRS Tumucumaque with carrot Brasilia